(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
In this study the stability of the rock has been evaluated to determine the most relevant factors affecting instability of slope . The discontinuity data collected from the field surveys was analyzed using stereograph projection. Sub horizontal-layer slopes of limestone rocks in Euphrates formation at Al-Najaf governorate, center of Iraq, presence of failures in slopes , Its from most to least rock fall, secondary toppling, and rolling. The degree and nature of hazard risk depend on properties of the rock discontinuity. This study recommends that rock instability is enhanced by fences barrier and building concrete walls and remove weak rocks.